Implementation of integrated reporting taxonomy of credit unions - Дземішкевич, Ігор Олександрович (Technology audit and production reserves, 2016)
XBRL taxonomy concept was defined during investigation of the possibility of introducing integrated reporting of credit unions. Issues towards the development and implementation of integrated reporting taxonomy were clearly defined. The model of implementation of integrated reporting taxonomy of credit unions was developed that will ensure the implementation of the principle of comparability of integrated reporting, and automated analysis to realize the integrated performance reporting of credit unions. Implementation of integrated reporting taxonomy of credit unions will solve the problem of comparability of integrated reporting as a single credit union for different periods and different credit unions. Implementation of comparability principle will promote integrated reporting process analysis by stakeholders, which is an important element of dialogue with society. A model for implementation of integrated reporting taxonomy of credit unions in Ukraine and creation of open National database of activities of credit unions is proposed. Sources of financing development, implementation and support of integrated reporting taxonomy of credit unions are defined. The results are valuable in terms of analysis practices of integrated reporting of credit unions. They can be taken as the basis for implementing integrated reporting taxonomy at national level and serve as a basis for further research.